Pelatihan Peningkatan Kapasitas dan Kreativitas Pengurus BUMDes Desa Pasar Terusan Kecamatan Muara Bulian Kabupaten Batang Hari - Adrian, Zulfina; Setiawan, Wahyu Juari; Yanti, Ovie (WIDA Publishing, 2023)
Pasar Terusan Village is one of the villages in Muara Bulian District, Batanghari Regency, with a relatively large population, thus has the potential to become a driving force in development, especially in Pasar Terusan Village. Pasar Terusan Village is located in a lowland area with extensive rice fields and plantations, which affect the economic patterns of local residents. The area of rice fields is ± 650 ha and is the largest land owned by the Muara Bulian district. Pasar Terusan Village is an expansion from Terusan Village and was once the economic mainstay of the village with the construction of a market on the banks of the Batanghari River. The people of Pasar Terusan Village, apart from being farmers, also have a livelihood as plantation farmers, both oil palm plantations and rubber plantations. The challenge for the Bumdes management to be able to develop their capacity and creativity in managing the potential they have, certainly provides a great opportunity for Bumdes to develop their businesses in order to improve the community's economy and add to the Village's PAD.